Perspectivas historiográficas sobre las Leyes de 1821 en Buenos Aires y su impacto en la definición de la ciudadanía política, 1821-1826 - Salvatto, Fabricio Gabriel (Historiografías, 2023)
The purpose of this article is the historiographic analysis of the 1821 Laws in Buenos Aires focusing on its foremost works. We shall compare interpretations, theoretical frameworks, and methodological approaches. Based on recent investigations, we also suggest some research topics to elucidate the central components singled out by historiography, as well as ways to deal with the political representation and citizenship in the context of the years 1821-1826. Keywords Historiographic approaches, 1921 Laws, Buenos Aires